Iron-based nanocrystalline ultrathin belt and preparation method thereof
Through constant tension bending annealing treatment and plasma nitriding treatment, the problems of poor service stability and insufficient magnetic performance of iron-based nanocrystalline alloys in harsh environments are solved, and good corrosion resistance and magnetic properties of iron-based nanocrystalline ultra-thin belts are achieved.
Patent Information
- Application Number
- CN202510071099.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-16
AI Technical Summary
Iron-based nanocrystal soft magnetic alloys, especially iron-based nanocrystal alloys with high saturation magnetic induction strength, have poor service stability in harsh use environments, and the existing annealing process is difficult to achieve uniform refinement of grains, affecting magnetic performance.
Iron-based nanocrystalline ultrathin belt was prepared by constant tension bending annealing treatment and plasma nitriding treatment. The constant tension bending annealing treatment helps grain refinement and lateral formation of magnetic domains, while the plasma nitriding treatment improves corrosion resistance.
The good corrosion resistance and magnetic properties of iron-based nanocrystalline ultra-thin belts are achieved, and the service stability in harsh environments is improved.
Smart Images

Figure CN119876760A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of iron-based nanocrystalline strips, in particular to an iron-based nanocrystalline ultra-thin strip and a preparation method thereof. Background Art
[0002] Using amorphous alloy as precursor, through appropriate annealing process, iron-based nanocrystalline alloy with α-Fe uniformly precipitated with a diameter of 10-20nm on the amorphous matrix is obtained. Compared with soft magnetic materials such as traditional silicon steel and electrical pure iron, it has more excellent soft magnetic properties, which is conducive to meeting the needs of "miniaturization, high efficiency and lightweight" of power electronic components. However, iron-based nanocrystalline soft magnetic alloys, especially iron-based nanocrystalline alloys with high saturation magnetic induction intensity, have poor service stability in harsh use environments.
[0003] The current annealing process usually places the amorphous alloy strip in an annealing furnace and performs heating and heat preservation treatment under an inert atmosphere to reduce the grain size and improve the magnetic properties of the resulting nanocrystalline alloy strip. However, the above annealing process is difficult to achieve uniform grain refinement, resulting in a limited degree of nanocrystallization of the alloy matrix, which affects the magnetic properties of the iron-based nanocrystalline ultra-thin strip. Based on this, an iron-based nanocrystalline ultra-thin strip and a preparation method thereof are proposed. Summary of the invention
[0004] In order to address the deficiencies of the prior art, the present invention provides an iron-based nanocrystalline ultra-thin belt and a preparation method thereof. Through constant tension bending annealing treatment and plasma nitriding treatment, the iron-based nanocrystalline ultra-thin belt has good corrosion resistance and magnetic properties.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: an iron-based nanocrystalline ultra-thin strip, comprising the following raw materials, measured in atomic percentage: Cu 0.5-1.5%, Si 12.0-13.5%, Co 0.5-1.0%, B 5.5-7.5%, Zr3.5-4.5%, Nb 0.5-1.5%, Y 0.5-1.0%, and the balance is Fe.
[0006] Preferably, the raw materials used are selected from pure iron (Fe content > 99.9%), pure silicon (Si content > 99.6%), pure copper (Cu content > 99.9%), ferroniobium (Nb content 65.5%, Si content 2.2%, Nb-Si-Fe total content > 99.5%), ferroboron (B content 19.6%, B-Fe total content > 99.5%), yttrium iron (Y content 68.4%, Y-Fe total content > 99.5%), ferrozirconium (Zr content 45.5%, Si content 32.4%, Zr-Si-Fe total content > 99.5%) and pure cobalt (Co content > 99.9%).
[0007] The present invention also provides a method for preparing an iron-based nanocrystalline ultra-thin strip, comprising the following steps:
[0008] (1) adding raw materials in proportion to a smelting furnace for melting, and skimming off the slag to obtain alloy liquid;
[0009] (2) The alloy liquid is made into amorphous strips by a single-roller strip spinning method;
[0010] (3) subjecting the amorphous strip to constant tension bending annealing to obtain a nanocrystalline strip;
[0011] (4) The nanocrystalline strip is subjected to plasma nitriding treatment to obtain an iron-based nanocrystalline ultra-thin strip.
[0012] Preferably, in step (2), in the single-roller belt-spinning method, the spray pressure is controlled to be 0.5-0.8 MPa, the distance between the nozzle and the copper roller is adjusted to be 0.5-1 mm, and the linear speed of the copper roller is 35-40 m / s.
[0013] Preferably, in step (2), the thickness of the amorphous strip is 25-35 μm.
[0014] Preferably, in step (3), the constant tension bending annealing treatment is specifically as follows: the amorphous strip passes through a pressure roller on one side, enters the annealing furnace through a left positioning roller, is bent by multiple sets of adjustment rollers, exits the annealing furnace through a right positioning roller, and passes through a pressure roller on the other side.
[0015] Preferably, in the annealing furnace, the amorphous strip is heated to 400-450°C in the first heating section, and its residence time in the first heating section is 40-60 min; the amorphous strip is heated to 550-600°C in the second heating section, and its residence time in the second heating section is 80-100 min.
[0016] Preferably, the amorphous strip between the pressing rollers on both sides is subjected to a horizontal pulling force of 5.5-6.5N.
[0017] Preferably, the bending angle of the amorphous strip formed in the adjusting roller is 40-60°.
[0018] Preferably, in step (4), the plasma nitriding treatment is specifically as follows: placing the nanocrystalline strip into a plasma nitriding furnace, with the furnace cover as the anode and the nanocrystalline strip as the cathode, and introducing ammonia into the furnace; controlling the ammonia pressure to be 1-5 Pa, the cathode voltage to be 0.6-0.7 kV, the conduction current to be 10-15 A, the nitriding temperature to be 200-230 ° C, and the nitriding time to be 40-55 min.
[0019] The present invention provides an iron-based nanocrystalline ultra-thin strip and a preparation method thereof, which has the following beneficial effects compared with the prior art:
[0020] The present invention applies tension, i.e. longitudinal tensile stress, to the amorphous strip during annealing, and heats the strip to allow the grains to undergo nucleation and growth. After the force is removed, it is equivalent to applying longitudinal compressive stress in the longitudinal direction of the strip, which helps the grains in the alloy matrix to compete with each other and tend to be arranged in the transverse direction, making it easier for magnetic domains to form in the transverse direction of the strip. Furthermore, the strip is continuously bent during annealing, which helps further refine the grains and reduce the pinning potential energy of the magnetic domains. Thus, the magnetization performance of the iron-based nanocrystalline ultra-thin strip can be improved.
[0021] The present invention performs plasma nitriding treatment on nanocrystalline strips, and the introduction of nitrides can greatly improve the corrosion resistance of the iron-based nanocrystalline ultra-thin strips, while the nitrides will affect the magnetic properties; however, during the plasma nitriding treatment, nitrogen atoms enter the iron lattice, causing the iron lattice to be distorted, thereby increasing the local average magnetic moment, and when zirconium atoms in a non-collinear structure are aggregated, the number of their low spin states is suppressed by reducing the nearest neighbor Fe-Fe pairs with antiferromagnetic coupling characteristics, thereby increasing the initial value of the local iron atom magnetic moment, thereby offsetting the magnetic dilution effect, and ultimately allowing the iron-based nanocrystalline ultra-thin strips to have good corrosion resistance and magnetic properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0023] Figure 1 This is a schematic diagram of the constant tension bending annealing process of the present invention;
[0024] Figure 2 This is a schematic diagram of the constant tension annealing process of the present invention;
[0025] Figure 3 This is the corrosion morphology of the iron-based nanocrystalline ultra-thin strip of the present invention. DETAILED DESCRIPTION
[0026] The following examples are used to explain the implementation methods of the present application in detail, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0027] Example 1
[0028] A method for preparing an iron-based nanocrystalline ultra-thin strip comprises the following steps:
[0029] (1) In terms of atomic percentage, Fe 72.5 Si 13.5 B 7.5 Zr 3.5 Co 0.5 Nb 1.5 Cu0.5 Y 0.5 Pure iron, pure silicon, pure copper, ferroniobium, ferroboron, ferroydtrium, ferrozirconium and pure cobalt are added into a smelting furnace for melting in a certain proportion, and an alloy liquid is obtained after skimming off the slag.
[0030] (2) The alloy liquid is made into an amorphous strip with a thickness of 25 μm by a single-roll strip spinning method;
[0031] In the single-roller belt-spinning method, the spray pressure was controlled to be 0.5 MPa, the distance between the nozzle and the copper roller was adjusted to be 0.5 mm, and the linear speed of the copper roller was 35 m / s.
[0032] (3) The amorphous strip is subjected to constant tension bending annealing treatment, i.e., the amorphous strip is passed through a pressure roller on one side, enters an annealing furnace through a left positioning roller, is bent by multiple sets of adjustment rollers with a bending angle of 40°, exits the annealing furnace through a right positioning roller, and passes through a pressure roller on the other side; during this period, the amorphous strip is heated to 450°C in the first heating section, and its residence time in the first heating section is 40 min; the amorphous strip is heated to 550°C in the second heating section, and its residence time in the second heating section is 100 min; the amorphous strip between the pressure rollers on both sides is controlled to be subjected to a horizontal tension of 5.5 N; and a nanocrystalline strip is obtained.
[0033] (4) Plasma nitriding treatment is performed on the nanocrystalline strip, i.e., the nanocrystalline strip is placed in a plasma nitriding furnace, the furnace cover is used as the anode, the nanocrystalline strip is used as the cathode, and ammonia gas is introduced into the furnace; the ammonia pressure is controlled to be 1 Pa, the cathode voltage is 0.7 kV, the conduction current is 10 A, the nitriding temperature is 230 ° C, and the nitriding time is 40 min; and an iron-based nanocrystalline ultra-thin strip is obtained.
[0034] Example 2
[0035] A method for preparing an iron-based nanocrystalline ultra-thin strip comprises the following steps:
[0036] (1) In terms of atomic percentage, Fe 74 Si 12 B 5.5 Zr 4.5 Co1N 0.5 Cu 1.5 Y1 ratio, pure iron, pure silicon, pure copper, ferroniobium, ferroboron, yttrium iron, ferrozirconium and pure cobalt are added into a smelting furnace for melting, and after skimming off the slag, an alloy liquid is obtained.
[0037] (2) The alloy liquid is made into an amorphous strip with a thickness of 35 μm by a single-roll strip spinning method;
[0038] In the single-roller belt-spinning method, the spray pressure was controlled to be 0.8 MPa, the distance between the nozzle and the copper roller was adjusted to be 1 mm, and the linear speed of the copper roller was 40 m / s.
[0039] (3) The amorphous strip is subjected to constant tension bending annealing treatment, i.e., the amorphous strip is passed through a pressure roller on one side, enters an annealing furnace through a left positioning roller, is bent by multiple sets of adjustment rollers with a bending angle of 60°, exits the annealing furnace through a right positioning roller, and passes through a pressure roller on the other side; during this period, the amorphous strip is heated to 450°C in the first heating section, and its residence time in the first heating section is 60 min; the amorphous strip is heated to 600°C in the second heating section, and its residence time in the second heating section is 80 min; the amorphous strip between the pressure rollers on both sides is controlled to be subjected to a horizontal tension of 6.5 N; and a nanocrystalline strip is obtained.
[0040] (4) Plasma nitriding treatment is performed on the nanocrystalline strip, i.e., the nanocrystalline strip is placed in a plasma nitriding furnace, the furnace cover is used as the anode, the nanocrystalline strip is used as the cathode, and ammonia gas is introduced into the furnace; the ammonia pressure is controlled to be 5 Pa, the cathode voltage is 0.6 kV, the conduction current is 15 A, the nitriding temperature is 200 ° C, and the nitriding time is 55 min; an iron-based nanocrystalline ultra-thin strip is obtained.
[0041] Example 3
[0042] A method for preparing an iron-based nanocrystalline ultra-thin strip comprises the following steps:
[0043] (1) In terms of atomic percentage, Fe 77 Si 12 B 5.5 Zr 3.5 Co 0.5 Nb 0.5 Cu 0.5 Y 0.5 Pure iron, pure silicon, pure copper, ferroniobium, ferroboron, ferroydtrium, ferrozirconium and pure cobalt are added into a smelting furnace for melting in a certain proportion, and an alloy liquid is obtained after skimming off the slag.
[0044] (2) The alloy liquid is made into an amorphous strip with a thickness of 30 μm by a single-roll strip spinning method;
[0045] In the single-roller belt-spinning method, the spray pressure was controlled to be 0.6 MPa, the distance between the nozzle and the copper roller was adjusted to be 0.7 mm, and the linear speed of the copper roller was 38 m / s.
[0046] (3) The amorphous strip is subjected to constant tension bending annealing treatment, i.e., the amorphous strip is passed through a pressure roller on one side, enters an annealing furnace through a left positioning roller, is bent by multiple sets of adjustment rollers with a bending angle of 45°, exits the annealing furnace through a right positioning roller, and passes through a pressure roller on the other side; during this period, the amorphous strip is heated to 400°C in the first heating section, and its residence time in the first heating section is 60 min; the amorphous strip is heated to 600°C in the second heating section, and its residence time in the second heating section is 80 min; the amorphous strip between the pressure rollers on both sides is controlled to be subjected to a horizontal tension of 6.0 N; and a nanocrystalline strip is obtained.
[0047] (4) Plasma nitriding treatment is performed on the nanocrystalline strip, i.e., the nanocrystalline strip is placed in a plasma nitriding furnace, the furnace cover is used as the anode, the nanocrystalline strip is used as the cathode, and ammonia gas is introduced into the furnace; the ammonia pressure is controlled to be 2 Pa, the cathode voltage is 0.6 kV, the conduction current is 12 A, the nitriding temperature is 230 ° C, and the nitriding time is 45 min; an iron-based nanocrystalline ultra-thin strip is obtained.
[0048] Example 4
[0049] A method for preparing an iron-based nanocrystalline ultra-thin strip comprises the following steps:
[0050] (1) In terms of atomic percentage, Fe 73.5 Si 12.5 B 6.5 Zr4Co1Nb1Cu1Y 0.5 Pure iron, pure silicon, pure copper, ferroniobium, ferroboron, ferroydtrium, ferrozirconium and pure cobalt are added into a smelting furnace for melting in a certain proportion, and an alloy liquid is obtained after skimming off the slag.
[0051] (2) The alloy liquid is made into an amorphous strip with a thickness of 30 μm by a single-roll strip spinning method;
[0052] In the single-roller belt-spinning method, the spray pressure was controlled to be 0.7 MPa, the distance between the nozzle and the copper roller was adjusted to be 0.8 mm, and the linear speed of the copper roller was 35 m / s.
[0053] (3) The amorphous strip is subjected to constant tension bending annealing treatment, i.e., the amorphous strip is passed through a pressure roller on one side, enters an annealing furnace through a left positioning roller, is bent by multiple sets of adjustment rollers with a bending angle of 50°, exits the annealing furnace through a right positioning roller, and passes through a pressure roller on the other side; during this period, the amorphous strip is heated to 420°C in the first heating section, and its residence time in the first heating section is 50 min; the amorphous strip is heated to 580°C in the second heating section, and its residence time in the second heating section is 90 min; the amorphous strip between the pressure rollers on both sides is controlled to be subjected to a horizontal tensile force of 6.0 N; and a nanocrystalline strip is obtained.
[0054] (4) Plasma nitriding treatment is performed on the nanocrystalline strip, i.e., the nanocrystalline strip is placed in a plasma nitriding furnace, the furnace cover is used as the anode, the nanocrystalline strip is used as the cathode, and ammonia gas is introduced into the furnace; the ammonia pressure is controlled to be 3.5 Pa, the cathode voltage is 0.6 kV, the conduction current is 12 A, the nitriding temperature is 220 ° C, and the nitriding time is 50 min; an iron-based nanocrystalline ultra-thin strip is obtained.
[0055] Comparative Example 1
[0056] A method for preparing an iron-based nanocrystalline ultra-thin ribbon is basically the same as Example 4, except that the nanocrystalline ribbon is not subjected to plasma nitriding treatment, and the obtained nanocrystalline ribbon is regarded as an iron-based nanocrystalline ultra-thin ribbon.
[0057] Comparative Example 2
[0058] A method for preparing an iron-based nanocrystalline ultra-thin strip comprises the following steps:
[0059] (1) In terms of atomic percentage, Fe 77.5 Si 12.5 B 6.5 Co1Nb1Cu1Y 0.5 Pure iron, pure silicon, pure copper, ferroniobium, ferroboron, ferroydtrium and pure cobalt are added into a smelting furnace for melting in a certain proportion, and the alloy liquid is obtained after skimming off the slag.
[0060] Steps (2) to (4) are the same as the corresponding steps in Example 4 to obtain an iron-based nanocrystalline ultra-thin strip.
[0061] Comparative Example 3
[0062] A method for preparing an iron-based nanocrystalline ultra-thin strip comprises the following steps:
[0063] (1) In terms of atomic percentage, Fe 73.5 Si 12.5 B 6.5 Zr4Co1Nb1Cu1Y 0.5 Pure iron, pure silicon, pure copper, ferroniobium, ferroboron, ferroydtrium, ferrozirconium and pure cobalt are added into a smelting furnace for melting in a certain proportion, and an alloy liquid is obtained after skimming off the slag.
[0064] (2) The alloy liquid is made into an amorphous strip with a thickness of 30 μm by a single-roll strip spinning method;
[0065] In the single-roller belt-spinning method, the spray pressure was controlled to be 0.7 MPa, the distance between the nozzle and the copper roller was adjusted to be 0.8 mm, and the linear speed of the copper roller was 35 m / s.
[0066] (3) subjecting the amorphous strip to annealing treatment, i.e., passing the amorphous strip through an annealing furnace; during the annealing treatment, the amorphous strip is heated to 420° C. in a first heating section, and its residence time in the first heating section is 50 min; the amorphous strip is heated to 580° C. in a second heating section, and its residence time in the second heating section is 90 min; and a nanocrystalline strip is obtained.
[0067] (4) Plasma nitriding treatment is performed on the nanocrystalline strip, i.e., the nanocrystalline strip is placed in a plasma nitriding furnace, the furnace cover is used as the anode, the nanocrystalline strip is used as the cathode, and ammonia gas is introduced into the furnace; the ammonia pressure is controlled to be 3.5 Pa, the cathode voltage is 0.6 kV, the conduction current is 12 A, the nitriding temperature is 220 ° C, and the nitriding time is 50 min; an iron-based nanocrystalline ultra-thin strip is obtained.
[0068] Comparative Example 4
[0069] A method for preparing an iron-based nanocrystalline ultra-thin strip comprises the following steps:
[0070] (1) In terms of atomic percentage, Fe 73.5 Si 12.5 B 6.5 Zr4Co1Nb1Cu1Y 0.5 Pure iron, pure silicon, pure copper, ferroniobium, ferroboron, ferroydtrium, ferrozirconium and pure cobalt are added into a smelting furnace for melting in a certain proportion, and an alloy liquid is obtained after skimming off the slag.
[0071] (2) The alloy liquid is made into an amorphous strip with a thickness of 30 μm by a single-roll strip spinning method;
[0072] In the single-roller belt-spinning method, the spray pressure was controlled to be 0.7 MPa, the distance between the nozzle and the copper roller was adjusted to be 0.8 mm, and the linear speed of the copper roller was 35 m / s.
[0073] (3) The amorphous strip is subjected to constant tension annealing treatment, i.e., the amorphous strip is inserted from a pressure roller on one side, enters an annealing furnace through a left positioning roller, exits the annealing furnace through a right positioning roller, and passes out from a pressure roller on the other side; during this period, the amorphous strip is heated to 420°C in the first heating section, and its residence time in the first heating section is 50 minutes; the amorphous strip is heated to 580°C in the second heating section, and its residence time in the second heating section is 90 minutes; the amorphous strip between the pressure rollers on both sides is controlled to be subjected to a horizontal tension of 6.0N; and a nanocrystalline strip is obtained.
[0074] (4) Plasma nitriding treatment is performed on the nanocrystalline strip, i.e., the nanocrystalline strip is placed in a plasma nitriding furnace, the furnace cover is used as the anode, the nanocrystalline strip is used as the cathode, and ammonia gas is introduced into the furnace; the ammonia pressure is controlled to be 3.5 Pa, the cathode voltage is 0.6 kV, the conduction current is 12 A, the nitriding temperature is 220 ° C, and the nitriding time is 50 min; an iron-based nanocrystalline ultra-thin strip is obtained.
[0075] Quality Inspection
[0076] 1. Saturation magnetic induction intensity: The saturation magnetic induction intensity of the iron-based nanocrystalline ultra-thin ribbon samples of Example 4 and Comparative Examples 1-4 was tested at room temperature using a vibrating sample magnetometer (VSM). The specific test results are shown in Table 1.
[0077] 2. Coercive force: The coercive force of the iron-based nanocrystalline ultra-thin ribbon samples of Example 4 and Comparative Examples 1-4 was tested at room temperature using a soft magnetic DC magnetic property measurement system. The specific test results are shown in Table 1.
[0078] Table 1 Saturation magnetic induction and coercivity
[0079]
[0080]
[0081] 3. Magnetic permeability: The inductance of the iron-based nanocrystalline ultra-thin strip samples of Example 4 and Comparative Examples 1-4 was tested using a 429A impedance analyzer and the magnetic permeability was calculated. The specific test results are shown in Table 2.
[0082] 4. Corrosion resistance: The iron-based nanocrystalline ultra-thin ribbon samples of Example 4 and Comparative Examples 1-4 were immersed in a 0.5 mol / L sodium chloride solution for 24 hours and then taken out for observation. Figure 3 And as shown in Table 2.
[0083] Table 2 Magnetic permeability and corrosion resistance
[0084] type Magnetic Permeability at 10kHz Corrosion Example 4 <![CDATA[1.82×10 4 ]]> Almost no corrosion products Comparative Example 1 <![CDATA[1.75×10 4 ]]> Large accumulation of corrosion products Comparative Example 2 <![CDATA[1.73×10 4 ]]> A few scattered accumulations of corrosion products Comparative Example 3 <![CDATA[1.44×10 4 ]]> / Comparative Example 4 <![CDATA[1.61×10 4 ]]> /
[0085] From the above table and combined Figure 3 It can be seen that:
[0086] (1) Compared with Example 4, the magnetic properties of the samples in Comparative Examples 1 and 2 did not decrease significantly, but their corrosion resistance deviated significantly, indicating that plasma nitridation treatment / zirconium doping has little effect on the magnetic properties, but can greatly improve the corrosion resistance of the samples.
[0087] (2) Compared with Example 4, the sample in Comparative Example 3 was not subjected to constant tension bending treatment, resulting in a significant decrease in its magnetic properties.
[0088] (3) Compared with Example 4, the sample in Comparative Example 4 was subjected to constant tension treatment but not to bending treatment, resulting in a decrease in its magnetic properties.
[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An iron-based nanocrystalline ultra-thin strip, characterized in that: Calculated by atomic percentage, the raw materials include: Cu 0.5-1.5%, Si 12.0-13.5%, Co 0.5-1.0%, B 5.5-7.5%, Zr 3.5-4.5%, Nb 0.5-1.5%, Y0.5-1.0%, and the balance is Fe.
2. The iron-based nanocrystalline ultra-thin ribbon according to claim 1, characterized in that: The raw materials used are selected from pure iron, pure silicon, pure copper, ferroniobium, ferroboron, ferroydtrium, ferrozirconium and pure cobalt.
3. The method for preparing the iron-based nanocrystalline ultra-thin ribbon according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) adding raw materials in proportion to a smelting furnace for melting, and skimming off the slag to obtain alloy liquid; (2) The alloy liquid is made into amorphous strips by a single-roller strip spinning method; (3) subjecting the amorphous strip to constant tension bending annealing to obtain a nanocrystalline strip; (4) The nanocrystalline strip is subjected to plasma nitriding treatment to obtain an iron-based nanocrystalline ultra-thin strip.
4. The method for preparing the iron-based nanocrystalline ultra-thin ribbon according to claim 3, characterized in that: In step (2), in the single-roller belt-spinning method, the spray pressure is controlled to be 0.5-0.8 MPa, the distance between the nozzle and the copper roller is adjusted to be 0.5-1 mm, and the linear speed of the copper roller is 35-40 m / s.
5. The method for preparing the iron-based nanocrystalline ultra-thin ribbon according to claim 3, characterized in that: In step (2), the thickness of the amorphous strip is 25-35 μm.
6. The method for preparing the iron-based nanocrystalline ultra-thin ribbon according to claim 3, characterized in that: In step (3), the constant tension bending annealing treatment is specifically as follows: the amorphous strip passes through a pressure roller on one side, enters the annealing furnace through a left positioning roller, is bent by multiple sets of adjustment rollers, exits the annealing furnace through a right positioning roller, and passes through a pressure roller on the other side.
7. The method for preparing the iron-based nanocrystalline ultra-thin ribbon according to claim 6, characterized in that: In the annealing furnace, the amorphous strip is heated to 400-450°C in the first heating section, and its residence time in the first heating section is 40-60 minutes; the amorphous strip is heated to 550-600°C in the second heating section, and its residence time in the second heating section is 80-100 minutes.
8. The method for preparing an iron-based nanocrystalline ultra-thin ribbon according to claim 6, characterized in that: The amorphous strip between the pressure rollers on both sides is subjected to a horizontal pulling force of 5.5-6.5N.
9. The method for preparing an iron-based nanocrystalline ultra-thin ribbon according to claim 6, characterized in that: The bending angle formed by the amorphous strip in the adjusting roller is 40-60°.
10. The method for preparing an iron-based nanocrystalline ultra-thin ribbon according to claim 3, characterized in that: In step (4), the plasma nitriding treatment is specifically as follows: placing the nanocrystalline strip into a plasma nitriding furnace, with the furnace cover as the anode and the nanocrystalline strip as the cathode, and introducing ammonia into the furnace; controlling the ammonia pressure to be 1-5 Pa, the cathode voltage to be 0.6-0.7 kV, the conduction current to be 10-15 A, the nitriding temperature to be 200-230 ° C, and the nitriding time to be 40-55 min.
Citation Information
Patent Citations
Thin ribbon of amorphous iron alloy
CN101194039A
Method of producing a strip of nanocrystalline material and device for producing a wound core from said strip
CN101371321A
Dust core, coil component, and method for producing dust core
CN104067358A
Amorphous strip and preparation method thereof, and preparation method of amorphous magnetic ring
CN115807198A
Nanometer crystal iron-base soft magnetic alloy
CN1162652A